Jacobian Elliptic Functions - 23.2 Definitions and Periodic Properties

From testwiki
Revision as of 12:00, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
23.2.E1 ω 1 + ω 2 + ω 3 = 0 subscript 𝜔 1 subscript 𝜔 2 subscript 𝜔 3 0 {\displaystyle{\displaystyle\omega_{1}+\omega_{2}+\omega_{3}=0}}
\omega_{1}+\omega_{2}+\omega_{3} = 0

omega[1]+ omega[2]+ omega[3] = 0
Subscript[\[Omega], 1]+ Subscript[\[Omega], 2]+ Subscript[\[Omega], 3] == 0
Skipped - no semantic math Skipped - no semantic math - -
23.2#Ex1 χ 1 = a ω 1 + b ω 3 subscript 𝜒 1 𝑎 subscript 𝜔 1 𝑏 subscript 𝜔 3 {\displaystyle{\displaystyle\chi_{1}=a\omega_{1}+b\omega_{3}}}
\chi_{1} = a\omega_{1}+b\omega_{3}

chi[1] = a*omega[1]+ b*omega[3]
Subscript[\[Chi], 1] == a*Subscript[\[Omega], 1]+ b*Subscript[\[Omega], 3]
Skipped - no semantic math Skipped - no semantic math - -
23.2#Ex2 χ 3 = c ω 1 + d ω 3 subscript 𝜒 3 𝑐 subscript 𝜔 1 𝑑 subscript 𝜔 3 {\displaystyle{\displaystyle\chi_{3}=c\omega_{1}+d\omega_{3}}}
\chi_{3} = c\omega_{1}+d\omega_{3}

chi[3] = c*omega[1]+ d*omega[3]
Subscript[\[Chi], 3] == c*Subscript[\[Omega], 1]+ d*Subscript[\[Omega], 3]
Skipped - no semantic math Skipped - no semantic math - -
23.2.E3 a d - b c = 1 𝑎 𝑑 𝑏 𝑐 1 {\displaystyle{\displaystyle ad-bc=1}}
ad-bc = 1

a*d - b*c = 1
a*d - b*c == 1
Skipped - no semantic math Skipped - no semantic math - -
23.2.E13 η 1 + η 2 + η 3 = 0 subscript 𝜂 1 subscript 𝜂 2 subscript 𝜂 3 0 {\displaystyle{\displaystyle\eta_{1}+\eta_{2}+\eta_{3}=0}}
\eta_{1}+\eta_{2}+\eta_{3} = 0

eta[1]+ eta[2]+ eta[3] = 0
Subscript[\[Eta], 1]+ Subscript[\[Eta], 2]+ Subscript[\[Eta], 3] == 0
Skipped - no semantic math Skipped - no semantic math - -
23.2.E14 η 3 ω 2 - η 2 ω 3 = η 2 ω 1 - η 1 ω 2 subscript 𝜂 3 subscript 𝜔 2 subscript 𝜂 2 subscript 𝜔 3 subscript 𝜂 2 subscript 𝜔 1 subscript 𝜂 1 subscript 𝜔 2 {\displaystyle{\displaystyle\eta_{3}\omega_{2}-\eta_{2}\omega_{3}=\eta_{2}% \omega_{1}-\eta_{1}\omega_{2}}}
\eta_{3}\omega_{2}-\eta_{2}\omega_{3} = \eta_{2}\omega_{1}-\eta_{1}\omega_{2}

eta[3]*omega[2]- eta[2]*omega[3] = eta[2]*omega[1]- eta[1]*omega[2]
Subscript[\[Eta], 3]*Subscript[\[Omega], 2]- Subscript[\[Eta], 2]*Subscript[\[Omega], 3] == Subscript[\[Eta], 2]*Subscript[\[Omega], 1]- Subscript[\[Eta], 1]*Subscript[\[Omega], 2]
Skipped - no semantic math Skipped - no semantic math - -